QUALITY ANALYSIS OF HEALTH SERVICES IN PUSKESMAS X BASED ON IMPORTANCE PERFORMANCE ANALYSIS METHOD - Mustara Mustara (Media Informasi, 2020)
Community Health Centers is one of the leading units in providing health services to the community. Along with the increasing demands of the community for quality health services, the accredited Community Health Centers must always improve the quality of its services. This study aims to find out how the quality of health services is seen in terms of service aspects, staff attitudes, and room conditions and attributes that are considered important by patients to improved. This research is a quantitative descriptive method to the Importance Performance Analysis approach. The study population was registered patients and utilizing health services provided by the X Community Health Center. The sample in this study used a quota sampling technique with 101 respondents. Data collection instruments using a questionnaire. The analysis used is the suitability of performance with its importance to all attributes, then the attributes described in the quadrant Importance Performance Analysis. The results showed the service variables, staff attitudes, and room conditions were categorized according to the expectations of their level of importance. Puskesmas need to encourage officers to be empathetic towards patients who will seek treatment, provide answers to any questions asked, have a patient waiting room equipped with a seat, have a clean corner room, and have a clean and non-slippery floor.